2016
DOI: 10.1590/1983-21252016v29n402rc
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pigeon Pea Inoculated With Rhizobium Isolated From Cowpea Trap Host Plants

Abstract: -Pigeon pea is an important protein source grown in several tropical and sub-tropical countries, and is considered a multi-purpose plant that is resistant to the conditions of the Brazilian Cerrado. Among the possible uses for cowpea, its use as a green manure, increasing soil nitrogen content through the association with diazotrophic bacteria, generically known as rhizobia, is noteworthy. The present work aimed to evaluate the efficiency of Rhizobium strains isolated from cowpea plants in the development of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
1
1
0
1
Order By: Relevance
“…These results further confirm the relevance of BNF for legume plants to grow and develop CAMPO;MENDES, 2007;GUIMARÃES et al, 2016). Santos et al (2017) observed that the single inoculation of Bradyrhizobium japonicum and A. brasilense and the co-inoculation with both significantly influenced the height of peanut plants, with the highest value obtained in the co-inoculated treatment.…”
Section: Plant Heightsupporting
confidence: 73%
See 1 more Smart Citation
“…These results further confirm the relevance of BNF for legume plants to grow and develop CAMPO;MENDES, 2007;GUIMARÃES et al, 2016). Santos et al (2017) observed that the single inoculation of Bradyrhizobium japonicum and A. brasilense and the co-inoculation with both significantly influenced the height of peanut plants, with the highest value obtained in the co-inoculated treatment.…”
Section: Plant Heightsupporting
confidence: 73%
“…This is the reason why it is so hard to establish an efficient rhizobium-peanut symbiosis (BORGES et al, 2007). The MT 15 strain has shown promising results in several studies conducted with different crops, such as pigeon pea (GUIMARÃES et al, 2016) and cowpea (SILVA et al, 2016 b), evidencing the potential for its use as an inoculant in Brazil.…”
mentioning
confidence: 99%
“…JáAlaswad et al (2019), sugerem o uso de estirpe de soja mutante de B. diazoefficiens, por garantir maior competitividade sobre os rizóbios nativos e formação de nódulos eficientes em guandu. Utilizando rizóbios isolados de feijão-caupi,Guimarães et al (2016) observaram potencial para uso em guandu BRS Mandarim. Em contrapartida,Carvalho et al (2008) relataram que embora tenha havido nodulação do guandu a partir de rizóbio específico para cultura da soja, ela não demonstrou eficiência simbiótica significativa.2.4.do nutriente no início do crescimento radicular podem aumentar os sítios de infecção e, portanto, promover maior formação de nódulos(TSAI et al, 1993), beneficiando a FBN.Em determinadas culturas leguminosas que apresentam nodulação tardia, fixam N durante um curto período ou apresentam baixo potencial de FBN, a aplicação de pequenas doses de nitrogênio tem funcionado como uma dose de arranque (MOREIRA;, como é o caso do feijoeiro-comum(TSAI et al, 1993;SOARES et al, 2016) e caupi(XAVIER et al, 2008).No guandu, a nodulação começa quinze dias após a semeadura e continua por até 120 dias, declinando devido à maior demanda de carboidratos na fase granífera (GODOY; SANTOS, 2011), o que presumivelmente resulta em menor oferta de fotoassimilados para os bacteroides e esqueletos de carbono para incorporação da NH 3 produzida pela nitrogenase.…”
unclassified